On-farm evaluation of the coconut hybrid, Malayan Yellow Dwarf x Vanuatu Tall for tolerance to the lethal yellowing disease of coconut in Ghana - S. K. Dery; J. Owusu-Nipah; E. Andoh-Mensah; B. N. Nuertey; J. Nkansah-Poku; R. Arthur; R. Philippe (International Coconut Community Journal, 2005)
The performance of the coconut hybrid, Malayan Yellow Dwarf x Vanuatu Tall (MYD x VTT) was assessed in Ghana for a period of 6-8 years. The hybrid has previously been identified as being tolerant to the devastating lethal yellowing disease known in Ghana as Cape Saint Paul Wilt Disease (CSPWD). CSPWD is the most important coconut disease in Ghana. It has destroyed approximately 11,000 ha of coconut in Ghana, causing economic hardship to thousands of people. Mortality due to CSPWD during the trial period was only 1.0%. The hybrid showed remarkable tolerance to CSPWD during the 8-year trial period. Mortality, inflorescence emergence and nut load depended largely on the level of farmers’ commitment to basic management practices. In well maintained farms, the hybrid performed two to three times better compared to farms where maintenance was poor.